Architecture and key technologies of the operation support system for intensive monitoring of provincial and local power communication network - Zhimin YANG; Danke HONG; Yu HUANG (Dianxin kexue)
In order to support the intensive monitoring of provincial and local power communication network,the existing operation support system was optimized and upgraded.A system architecture which takes the communication dispatcher as information center was presented,and several key technologies of monitoring,control and resource scheduling were developed.The achievements were widely used in the power grid companies of five provinces in southern China.The results show that both the operation efficiency and the level of safe operation of the intensive monitoring for provincial-local power communication network has been significantly improved,which provides more reliable and higher quality communication support for both the safe and stable operation of the power grid and the digital transformation of the company.